Dictionary of energy efficiency technologies - Hordeski, Michael F. (Fairmont Press ; Distributed by Marcel Dekker, 2004)
This comprehensive reference addresses the diverse topics that form the backbone of energy efficiency in a timesaving dictionary format. Entries include a broad range of key topics.
Keywords: Energy consumption -- Dictionaries.; elektronické knihy; electronic books